2019
DOI: 10.21873/anticanres.13721
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Application of Diverse Marine-derived Natural Products in Cancer Therapy

Abstract: Natural products (NPs) are useful sources of bioactive compounds and play important roles in the development and discovery of new drugs for diverse human diseases. Most natural products originate from terrestrial species, but diverse marine organisms are another source of new agents for cancer therapy. Natural products derived from marine organisms show diverse pharmacological activities via bioactive secondary metabolites. They regulate biological activities, such as cell proliferation, cell viability, induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…Accumulating evidence indicates that natural products are useful sources of secondary metabolites, and they play an important role in cancer therapy [ 7 , 29 ]. It has been reported that ilimaquinone can inhibit the growth of various cancer cells [ 13 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that natural products are useful sources of secondary metabolites, and they play an important role in cancer therapy [ 7 , 29 ]. It has been reported that ilimaquinone can inhibit the growth of various cancer cells [ 13 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, paclitaxel from Taxus brevifolia has been approved by the FDA for treating breast cancer and ovarian cancer since 1992 [ 6 ]. Recently, secondary metabolites from marine organisms have garnered considerable attention owing to their therapeutic application in cancer therapies [ 7 ]. Previous studies have shown that polysaccharides from red seaweed inhibit cell growth by inducing apoptosis in various cancer cell lines, including breast cancer [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of molecular targets and carcinogenesis mechanisms allows a further exploitation of natural anti-cancer agents efficient in one particular step of all core steps from carcinogenesis [192] . The main targets where anti-cancer therapeutics usually work could be: preventing cell resistance to apoptosis or cell cycle checkpoints modifications, directly protecting DNA from damage or enhancing DNA repair mechanisms, and/or protecting against oxidative stress and reactive oxygen species (ROS) [93,[193][194][195][196] . Natural compounds have gained interest due to the increase of cancer resistance and undesirable side effects among synthetic choices.…”
Section: Bioactive Compounds Against Cancermentioning
confidence: 99%
“…There are about 350,000 plant species on earth, which have been a major source of medicines for a long time. The Chinese began to use herbs to treat cancer, as well as cardiovascular and other incurable diseases, several thousands of years ago [9,10]. Astragalus roots which have been used in traditional Chinese medicine include those of Astragalus mongholicus and A. membranaceus [11].…”
Section: Introductionmentioning
confidence: 99%